Dissidence and Persecution in Byzantium
1 online resource.
Keywords: This volume brings together papers focused on the issues of dissidence and persecutions in early and middle Byzantine period - from Constantine to late eleventh century. They explore a variety of problems on the imperial centre and periphery such as: the Byzantine and Jewish relations, the iconoclastic dispute, papal-imperial relations and frictions, loyalty and dissidence on the imperial periphery, etc. The aim of the volume is to explore different perspectives of dissent and persecution, the reasons driving dissent and causing persecutions, as well as their perceptions and depictions in the Byzantine literature.